2022
DOI: 10.1111/famp.12807
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of postdivorce intervention programs for children: A meta‐analytical review

Abstract: Preventive postdivorce interventions aim to help children cope with divorce and promote their adjustment. Nevertheless, questions remain regarding the concrete outcomes of these interventions and the intervention characteristics that influence them. This meta‐analysis of 30 studies analyzes the efficacy of postdivorce interventions on children's symptomatology, personal resources, and adaptation to divorce. Likewise, it explores whether the intervention impacts the putative mediators from the family context an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 97 publications
0
5
0
Order By: Relevance
“…Second, our findings suggest that resources should be diverted toward supporting families at an early stage of parental separation, for example, family-based support at child health care centers. Prior research has suggested that interparental conflicts explain a substantial part of the negative effect associated with parental separation; thus, interventions that improve children’s coping with transitioning through parental separation may be most beneficial . Third, our finding that adolescence appears to be a critical period for intervention needs further research.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…Second, our findings suggest that resources should be diverted toward supporting families at an early stage of parental separation, for example, family-based support at child health care centers. Prior research has suggested that interparental conflicts explain a substantial part of the negative effect associated with parental separation; thus, interventions that improve children’s coping with transitioning through parental separation may be most beneficial . Third, our finding that adolescence appears to be a critical period for intervention needs further research.…”
Section: Discussionmentioning
confidence: 83%
“…Prior research has suggested that interparental conflicts explain a substantial part of the negative effect 36 associated with parental separation; thus, interventions that improve children’s coping with transitioning through parental separation may be most beneficial. 12 Third, our finding that adolescence appears to be a critical period for intervention needs further research. We know that the transition to adulthood is a sensitive time both for parents and children; however, many interventions have been targeted at early years.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…However, the various ways online parent education programs accomplish specific goals in the family courts have not been clearly articulated. In addition, although there is evidence that online programs can meet the needs of multiple populations (see Fackrell et al, 2011;Herrero et al, 2023;Sandler et al, 2024;Schramm & McCaulley, 2012), not all online parent education programs are effective. Illustratively, two randomized trials failed to find strong support that commonly used online parent education programs accomplish a range of goals such as improving family functioning, child well-being, resolution of legal agreements, or relitigation (Rudd et al, 2015(Rudd et al, , 2017Tomlinson et al, 2023).…”
Section: State Of the Science-promises And Cautions Of Online Parent ...mentioning
confidence: 99%